ANALYSIS OF ASSET GROWTH AND PROFIT GROWTH THROUGH SUPPLY CHAIN MANAGEMENT TOWARD COMPANY VALUE - Saputra, Jumadil; Badruzaman, Jajang; Ridho, Adil (International Journal of Supply Chain Management, 2019)
The purpose of this study was to determine the effect of asset growth and profit growth on firm value. The object of research is financial reports issued by finance companies from 2015 to 2017, which are as many as 45 companies listed on the IDX. Analysis of the data used is path analysis and data processing used using the SPSS program. The results of data processing show that asset growth and profit growth have a significant effect on firm value. Partially asset growth has a significant effect on firm value, but earnings growth has a significant negative effect on firm value. The relationship between asset growth and profit growth has a negative relationship.